MEDIA DIFUSI EFEKTIF UNTUK SOSIALISASI KEBIJAKAN AKSELERASI PENGEMBANGAN PASAR TRADISIONAL MENUJU SEMI MODERN - Saudah Saudah (Universitas Merdeka Malang, 2016)
The development of traditional market to become a modern one requires a comprehensive participative approach involving the concerned stakeholders. All parties such as central and local government agencyalong with market traders should come together to sit one table for discussing the matter. By doing so, the parties can voice their interest; the government agency can socialize the proposed policy while the traditional market traders respond to it attentively. Besides face-to-face communication means, the government can make use of another means of communication media such as letters, and paid mass advertising to win public appreciation. This shows the crucial role of mass media communication in propagating government policies. Publicizing government policy is a means to develop the parties commitment to device norms, rules, and values that are to be institutionalized in an attempt to have the related policies sustainable. It is through this means the proposed government project eventually be implemented well. Added to that, it will open opportunity for traditional merchants to defend as well as develop their venue in such way so that they can adapt to the changing social and political environments.DOI: https://doi.org/10.26905/pjiap.v1i1.435